1993
DOI: 10.1021/j100152a020
|View full text |Cite
|
Sign up to set email alerts
|

Tetraarylborates {[Ar]4B-}: estimation of oxidation potentials and reorganization energies from electron-transfer rates

Abstract: Photoinduced electron transfer in ion pairs where the anion is a tetrasubstituted borate gives a boranyl radical. This species is reactive. When the boranyl radical contains an alkyl group, the carbon-boron bond cleaves in ca. 250 fs. The lifetime of tetraarylboranyl radicals is greater than 40 ps. The short lifetime of boranyl radicals prohibits measurement of the oxidation potentials of borates by electrochemical methods. These quantities were estimated by application of Marcus electron-transfer theory, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 2 publications
1
46
0
Order By: Relevance
“…The decomposition of the alkyltriphenylborate radical occurs with the rate approximately 10 12 s À1 and eliminates the possibility of proton transfer from an oxidized electron donor to an acceptor radical ion. [21] In other words, the butyltriphenylborate anion should behave similarly to PTAA AS. The evidences of these similarities are shown in Figure 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…The decomposition of the alkyltriphenylborate radical occurs with the rate approximately 10 12 s À1 and eliminates the possibility of proton transfer from an oxidized electron donor to an acceptor radical ion. [21] In other words, the butyltriphenylborate anion should behave similarly to PTAA AS. The evidences of these similarities are shown in Figure 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…The thermodynamically meaningful oxidation potential can be established as it was mentioned earlier, using indirect, kinetic method described by Murphy and Schuster 20b. The oxidation potentials measured electrochemically and kinetically differ by about 0.3 V. Therefore, the obtained electrochemical values for both components of photoredox pairs may have only approximate thermodynamic meaning yet, allows to estimate roughly Δ G el for the PET process.…”
Section: Resultsmentioning
confidence: 98%
“…This makes these systems attractive for investigation of electron transfer theories. In an attempt to obtain accurate and thermodynamically meaningful values for the oxidation potentials of tetraarylborates, Schuster and coworkers developed a kinetic method20 and found that the application of the Rehm–Weller relationship leads to an overestimation of the oxidation potentials when compared with those obtained from the classical Marcus relationship.…”
Section: Introductionmentioning
confidence: 99%
“…The photochemistry of the dye/aromatic thiocarboxylic acid photoredox pair is also very complex 20,28. In the case of alkyltriphenylborate salts as electron donors, the alkyl radical is formed as a result of the rapid cleavage of the alkyl boron bond of the boranyl radical obtained as a result of the photoinduced electron transfer from a borate anion to the excited state of an electron acceptor 22,23,29. The initiation of the polymerization for a dye/ N , N′ ‐dialkoxy‐4,4′‐bipyridinium dication systems results from the cleavage of the nitrogen‐oxygen bond of a N , N′ ‐dialkoxy‐4,4 ′ ‐bipyridine radical cation obtained after electron transfer from the excited dye molecule to the ground state of a N , N′ ‐dialkoxy‐4,4 ′ ‐bipyridinium salt.…”
Section: Resultsmentioning
confidence: 99%